Associations of race, mechanism of injury, and neighborhood poverty with in-hospital mortality from trauma: A population-based study in the Detroit metropolitan area. Issue 39 (September 2018) - Loberg, Jacey A.; Hayward, R. David; Fessler, Mary; Edhayan, Elango
Abstract : Abstract: Health disparities based on race and socioeconomic status are a serious problem in the US health care system, but disparities in outcomes related to traumatic injury have received relatively little attention in the research literature. This study uses data from the State Inpatient Database for Michigan including all trauma-related hospital admissions in the period from 2006 to 2014 in the Detroit metropolitan area (N = 407, 553) to examine the relationship between race (White N = 232, 109; African American N = 86, 356, Hispanic N = 2709, Other N = 10, 623), socioeconomic background, and in-hospital trauma mortality. Compared with other groups, there was a higher risk of mortality after trauma among African Americans (odds ratio [OR] = 1.20, P  < .001), people living in high-poverty neighborhoods (OR = 1.01, P  < .001), and those enrolled in public health insurance programs (OR = 1.53, P  < .001). African American patients were more likely to have had traumatic injuries caused by certain mechanisms with higher risk of death ( P  < .001). After controlling for mechanism alone in multiple logistic regression, African American race remained a significant predictor of mortality risk (OR = 1.12, P  < .001). After additionally controlling for the socioeconomic factors of insurance status and neighborhood poverty levels, there were no longer any significant differences between racial groups in terms of mortality (OR = 0.99, P  = .746). These results suggest that in this population the racial inequalities in mortality outcomes were fully mediated by differences between groups in the pattern of injuries suffered and differences in risk based on socioeconomic factors.